Does the real interest parity hypothesis hold? Evidence for developed and emerging markets - Alex Luiz Ferreira; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2003)
Evidence is presented on the Real Interest Parity Hypothesis for a set of emerging and developed countries. This is done by carrying out a set of unit-root tests on the real interest differentials with respect to Germany and the US. Our results support the hypothesis of a rapid reversion towards a zero differential for developed countries and towards a positive one for emerging markets. An important result is that this adjustment tends to be highly asymmetric and markedly different for developed and emerging countries. Our evidence reveals a high degree of market integration for developed countries and highlights the importance of risk premia for emerging markets.
Keywords: F32; F21; C22; 330; Real Interest Rate Differentials; Market Integration; Unit Roots; Asymmetric adjustment; Zinsparität; Realzins; Marktintegration; Unit Root Test; Vergleich; Industriestaaten; Schwellenländer